2022
DOI: 10.3389/fcell.2022.859582
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant SKP1 Expression: Diverse Mechanisms Impacting Genome and Chromosome Stability

Abstract: The S-phase Kinase-Associated Protein 1 (SKP1) is a core component of the SKP1, Cullin 1, F-box protein (SCF) complex, an E3 ubiquitin ligase that serves to poly-ubiquitinate a vast array of protein targets as a signal for their proteasomal degradation, thereby playing a critical role in the regulation of downstream biological processes. Many of the proteins regulated by SKP1 and the SCF complex normally function within pathways that are essential for maintaining genome stability, including DNA damage repair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
(141 reference statements)
1
5
0
Order By: Relevance
“…Through this mechanism, FBXO32 negatively regulates SKP1 activity, which may influence cell cycle progression and other cellular processes relevant to glioma development. Although the roles of SKP1 in chromosome instability have been largely revealed, 21,22 interestingly, the previous study has demonstrated that SKP1 acts as a tumor promoter via enhancing colorectal cancer stemness, 23 this is consistent with our results showing its promoting effects in glioma progression as tumor stemness has been elucidated as one of the root of tumor progression. 24 The identification of the FBXO32-SKP1 axis provides new insights into the regulation of glioma cell behaviors and offers a potential avenue for therapeutic intervention.…”
Section: Discussionsupporting
confidence: 90%
“…Through this mechanism, FBXO32 negatively regulates SKP1 activity, which may influence cell cycle progression and other cellular processes relevant to glioma development. Although the roles of SKP1 in chromosome instability have been largely revealed, 21,22 interestingly, the previous study has demonstrated that SKP1 acts as a tumor promoter via enhancing colorectal cancer stemness, 23 this is consistent with our results showing its promoting effects in glioma progression as tumor stemness has been elucidated as one of the root of tumor progression. 24 The identification of the FBXO32-SKP1 axis provides new insights into the regulation of glioma cell behaviors and offers a potential avenue for therapeutic intervention.…”
Section: Discussionsupporting
confidence: 90%
“…The signature genes SKP1 and BAP1were identified and validated in this study. SKP1, a part of the E3 ubiquitin ligase complex that leads to protein degradation, plays an important role in maintaining genome and chromosome stability [ 44 , 45 ]. It is downregulated in the brains of patients with sporadic Parkinson’s disease (PD) and plays a neuroprotective role in the adult brain [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The markedly down-regulated genes in the DHEA group mainly focused on cell cycle. S-phase Kinase-Associated Protein1 (SKP1) is a core component of the Skp, Cullin, F-box containing complex, an E3 ubiquitin ligase that participates in a variety of cellular processes (THOMPSON et al 2022). It was reported that reduced SKP1 expression induced chromosomal instability in both benign and malignant tumors (LEPAGE et al 2021).…”
Section: Discussionmentioning
confidence: 99%